Masalah Gizi Pada Bayi Baru Lahir Di Bangka Belitung Selama Periode 2019-2023: Nutritional Problems in Newborn Babies in Bangka Belitung during the 2019-2023 period - Efrizal, Wiwin (Program Studi Gizi, Fakultas Kesehatan Masyarakat, Universitas Binawan, 2024)
The integrated nutritional information system (Sigizi Terpadu), known as e-PPGBM, developed by the Ministry of Health can be useful as a data source for observing nutritional problems in certain target groups. Newborn baby data in e-PPGBM can provide an overview of nutritional and health conditions during pregnancy. This research was designed in a cross-sectional manner by downloading data on newborns in the 2019–2023 period (last 5 years) in the Bangka Belitung Islands Province from the e-PPGBM application. The data were analyzed descriptively and graphically. The number of newborns has decreased every year, ranging from 7.0–17.5% with a sex ratio of 1.17–1.23. There is a gap in the reported numbers between e-PPGBM and family health profiles each year, up to 35% in 2023. The prevalence of underweight over the last 5 years ranged from 12.7–14.4% and increased during the 2020–2021 pandemic by 1.7% for underweight and 1.5% for stunted, but wasting decreased by 1.9%. The incidence of underweight and stunted babies is more common in boys, while wasting is more common in baby girls. The decrease in the prevalence of wasting in the 2019–2023 period is assumed to be due to a decrease in the number of babies reported in the e-PPGBM application, although the prevalence of underweight and stunted increases in the 2019–2023 period but is lower than the 2023 SKI results. Appropriate nutritional and health interventions need to be implemented during pregnancy and when the new baby is born.